THE IMPACT OF AI-BASED LESSON STUDY AND EDUCATIONAL GAMES ON STUDENTS’ ABILITY TO ANALYZE PROBLEMS - Aminatur Rosyidah; Elok Hidayah; Ahmad Najam K.D; Novi Ismiasih (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2025)
The integration of artificial intelligence (AI) and educational games in education, particularly in ecology, has been the focus of this study to improve students' analytical skills on environmental issues. This study aims to explore the impact of lesson study based on AI and educational games on critical thinking and problem solving skills. The method used was qualitative with a case study approach, involving 30 grade X students of MA Al-Amiriyyah, as well as key informants such as principals, teachers, and students. Data were collected through observation, semi-structured interviews, and document analysis, then analyzed interpretatively. The results showed that the combination of AI and educational games significantly improved student engagement, understanding of ecological concepts, and analytical skills, especially for students who actively participated. AI enables personalization of learning, while educational games create interactive experiences that encourage critical thinking. Observations revealed that technology-based activities, such as group discussions and educational games, were more effective in improving understanding than conventional methods. Student learning outcomes also improved, with higher post-test scores, especially for students who initially had low scores. However, challenges such as over-reliance on technology and facility gaps need to be addressed. Overall, this study highlights.